Active deformation and Plio-Pleistocene fluvial reorganization of the western Kura fold–thrust belt, Georgia: implications for the evolution of the Greater Caucasus Mountains. (13th April 2021) - Sukhishvili, Lasha; Forte, Adam M.; Merebashvili, Giorgi; Leonard, Joel; Whipple, Kelin X.; Javakhishvili, Zurab; Heimsath, Arjun; Godoladze, Tea
Abstract: Since Plio-Pleistocene time, southward migration of shortening in the eastern part of the Greater Caucasus into the Kura foreland basin has progressively formed the Kura fold–thrust belt and Alazani piggyback basin, which separates the Kura fold–thrust belt from the Greater Caucasus. Previous work argued for an eastward propagation of the Kura fold–thrust belt, but this hypothesis was based on coarse geological maps and speculative ages for units within the Kura fold–thrust belt. Here we investigate the initiation of deformation within the Gombori range in the western Kura fold–thrust belt and evaluate this eastward propagation hypothesis. Sediments exposed in the Gombori range have a Greater Caucasus source, despite the modern drainage network in the NE Gombori range, which is dominated by NE-flowing rivers. Palaeocurrent analyses of the oldest and youngest syntectonic units indicate a switch happened between 2.7 Ma and 1 Ma from dominantly SW-directed flow to palaeocurrents more similar to the modern drainage network. A single successful 26 Al– 10 Be burial date indicates the youngest syntectonic sediments are 1.0 ± 1.0 Ma, which, while not a precise age, is consistent with original mapping suggesting these sediments are of Akchagylian–Apsheronian (2.7–0.88 Ma) age. These results, along with recent updated dating of thrust initiation in the eastern Kura fold–thrust belt, suggest that deformation within the Kura fold–thrust belt initiated synchronously or nearly synchronously along-strike. We additionally use topographic analyses to show that the Gombori range continues to be a zone of active deformation.